Our community - Dorothy (ed.); Mial, Curtis (ed.) (New York, 1960)
For many years those of us who have been interested in the field of community development have recognized the need for an informal "course" which would help adults understand the nature of their local community and become better equipped to work with other citizens in develop ing rational solutions to its problems. Ideally, such a course should be designed for, and conducted by, lay people. For in a democratic society the identification of community needs, the establishment of priorities for these needs, and the mobili zation of resources to meet these needs, is, in the last analysis, the responsibility of its citizens. This series of study-discussion programs entitled Our Community can be described as a course in community citizenship.
Keywords: Community development